Synergistic Doping and Intercalation: Realizing Deep Phase Modulation on MoS2 Arrays for High‐Efficiency Hydrogen Evolution Reaction. Issue 45 (24th September 2019) - Deng, Shengjue; Luo, Mi; Ai, Changzhi; Zhang, Yan; Liu, Bo; Huang, Lei; Jiang, Zheng; Zhang, Qinghua; Gu, Lin; Lin, Shiwei; Wang, Xiuli; Yu, Lei; et al.
Abstract: A synergistic N doping plus PO4 3− intercalation strategy is used to induce high conversion (ca. 41 %) of 2H‐MoS2 into 1T‐MoS2, which is much higher than single N doping (ca. 28 %) or single PO4 3− intercalation (ca. 10 %). A scattering mechanism is proposed to illustrate the synergistic phase transformation from the 2H to the 1T phase, which was confirmed by synchrotron radiation and spherical aberration TEM. To further enhance reaction kinetics, the designed (N, PO4 3− )‐MoS2 nanosheets are combined with conductive vertical graphene (VG) skeleton forming binder‐free arrays for high‐efficiency hydrogen evolution reaction (HER). Owing to the decreased band gap, lower d‐band center, and smaller hydrogen adsorption/desorption energy, the designed (N, PO4 3− )‐MoS2 /VG electrode shows excellent HER performance with a lower Tafel slope and overpotential than N‐MoS2 /VG, PO4 3− ‐MoS2 /VG counterparts, and other Mo‐base catalysts in the literature. Abstract : An N‐doping plus PO4 3− intercalation strategy is used to induce high conversion (ca. 41 %) of 2H‐MoS2 into 1T‐MoS2, which is much higher than single N‐doping or PO4 3− intercalation (ca. 28 % and ca. 10 %, respectively). A scattering mechanism is proposed to illustrate the synergistic phase transformation from 2H phase to 1T phase, confirmed by synchrotron radiation and spherical aberration TEM.